Investigation of Housing Purchase Tendencies of Individuals in Türkiye According to Selected Socioeconomic Variables (Third Sector Social Economic Review, 2026)
This study aims to analyze the housing purchase tendencies of individuals in Türkiye according to their socioeconomic status. In this regard, an online survey was administered to 757 participants living in various provinces of Türkiye, selected through a purposive sampling method. Pearson’s Chi-Square test was employed to analyze the relationship between housing purchase tendencies and socioeconomic variables. In tables where expected cell frequencies fell below 5, Fisher’s Exact Test was utilized. Additionally, Cramér’s V effect size values were calculated for all hypotheses. Among the participants, 51,0% were male, 39,1% were in the 36-45 age group, 73,8% were married, 47,7% were held a bachelor’s degree, and 47,0% were public sector employees. While 52,6% of the participants owned their current residence, the rate of participants where either themselves or their spouse owned at least one property was 68,6%. The proportion of those considering a housing purchase was 39,4%, while 31,2% were not considering it. The primary reason for 23,9% of those intending to purchase was the desire for investment. Conversely, for 32,7% of those not considering a purchase, the reason was a lack of economic power to meet the payments. The limitations of the study include the inability to diversify the distribution of participants' education levels and provincial statuses more equitably, and the measurement of housing purchase tendencies using a single-item scale. Statistically significant differences were found between individuals' housing purchase tendencies and their age, education, income, and employment status. The study suggests facilitating access to finance for non-homeowners seeking residential property for housing purposes. Furthermore, it is recommended that the Housing Development Administration (TOKİ) and Emlak Konut prioritize housing production for low- and middle-income groups and non-homeowner families. Other suggestions include auditing the health and durability standards of housing and providing state-led support regarding the financial, legal, and technical aspects of the housing transaction process.
Keywords: Housing; home ownership; purchasing housing; tendency to purchase housing; socioeconomic status